Implementasi E-Office Sabdopalon Jombang Sebagai Langkah Menuju Pemerintahan Digital - Erika Patricia; Hayat Hayat; Suyeno Suyeno (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2023)
In an effort to improve the quality of public service, the Jombang district is one of the most Indonesia areas to participate in the development of a digitisation of service. The latest innovation developed by the Jombang district administration is the e-office sabdopalon Jombang, which is the system for deso data news administration and online services that an android user can access through www.sabdopalon. Jomkakab. go.id. Researchers use qualitative research methods through a descriptive analysis approach, as with researchers' descriptive analysis it can easily get information and views on the research object. In research implementation of the e-office sabdopalon jombang as a step to the digital government, researchers use Charles Jones' theory of organization, the cooperation of the Jombang district government with communications and information services, and the public can access the 24-hour sabdopalon Jombang e-office with the support of Internet network and other electronics. In interpretation, some villages in the Jombang county have yet to include call center in information delivery. For application, it has been effective because people can easily access the features of the e-office sabdopalon Jombang, only Internet networks that haven't reached the far reaches of villages in the Jombang district are a problem in implementing it.